Comparison of bone healing, as assessed by computed tomography, following tibial tuberosity advancement in dogs with and without autogenous cancellous bone grafts. Issue 5 (3rd September 2017) - James, DR; Webster, N; White, JD; Marchevsky, AM; Cashmore, RG; Havlicek, M; Fearnside, S; Black, AP
Abstract: AIMS: To objectively compare measures of bone healing, using computed tomography (CT) in dogs following bilateral tibial tuberosity advancement (TTA), between tibiae treated with and without autogenous cancellous bone grafts. METHODS: Ten dogs with bilateral cranial cruciate ligament disease requiring surgical stabilisation were prospectively recruited to undergo single-session bilateral TTA, with only one, randomly assigned, tibia receiving bone graft in the osteotomy deficit. Bone healing at the osteotomy site was assessed using CT performed 38–70 days post-operatively. CT images were evaluated using both objective measurements of osseous bridging and subjective evaluation by six radiologists. Repeated measures ANOVA was used to compare the objective outcomes between the grafted and non-grafted tibiae. RESULTS: The mean percentage of the osteotomy deficit bridged at the lateral cortex was greater in grafted (77.6, SD 35.2%) compared to non-grafted (63.0, SD 36.5%) tibiae (p=0.001), but did not differ at the medial cortex (p=0.1). The mean minimum callus width was greater in grafted (7.2, SD 3.3 mm) compared to non-grafted (3.6, SD 2.9 mm) tibiae (p<0.001). There was no difference in mean attenuation (measured in Hounsfield units) of the callus between grafted and non-grafted tibiae (p=0.5). The grafted tibia was deemed to have superior bone healing in 50/60 subjective assessments made by radiologists. CONCLUSIONS: Superior osseous bridging was detected by CT analysis following TTA using autogenous cancellous bone grafts compared with no graft. This was shown by greater bridging percentage at the lateral cortex and formation of a broader callus. Qualitative assessments made by six radiologists also supported the conclusion that bone healing was improved by use of autogenous cancellous bone graft. CT was a useful method for assessing evidence of bone healing following TTA. CLINICAL RELEVANCE: These findings justify the application of autogenous cancellous bone graft to augment healing following TTA in dogs.